Understanding Perception and Factors Influencing Private Voluntary Health Insurance Policy Subscription in the Lucknow Region - Tanuj Mathur; Ujjwal Kanti Paul; Himanshu Narayan Prasad; Subodh Chandra Das (Kerman University of Medical Sciences, 2015)
Background Health insurance has been acknowledged by researchers as a valuable tool in health financing. In spite of its significance, a subscription paralysis has been observed in India for this product. People who can afford health insurance are also found to be either ignorant or aversive towards it. This study is designed to investigate into the socio-economic factors, individuals' health insurance product perception and individuals' personality traits for unbundling the paradox which inhibits people from subscribing to health insurance plans. Methods This survey was conducted in the region of Lucknow. An online questionnaire was sent to sampled respondents. Response evinced by 263 respondents was formed as a part of study for the further data analysis. For assessing the relationships between variables T-test and F-test were applied as a part of quantitative measuring tool. Finally, logistic regression technique was used to estimate the factors that influence respondents' decision to purchase health insurance. Results Age, dependent family members, medical expenditure, health status and individual's product perception were found to be significantly associated with health insurance subscription in the region. Personality traits have also showed a positive relationship with respondent's insurance status. Conclusion We found in our study that socio-economic factors, individuals' product perception and personality traits induces health insurance policy subscription in the region.